O cortiço: possibilidades de leitura em sala de aula do Ensino Médio - SOARES, Débora de Brito (UNIFAP – Universidade Federal do Amapá, 2022)
This research aims to reflect about the importance of using literary texts in literature classes, relying, specifically, on the work The Tenement of Aluísio de Azevedo. The composition was chosen for making a direct observation of reality. This study focus had his awakening from the experience of researchers in the Supervised Internship discipline in which they came across with literature teaching that left aside the reason for being of literary study, reading the compositions. In this way, began fieldwork with the monitoring of literature classes in a class of 2nd year of high school in the state school Augusto Antunes, in the city of Santana, state of Amapá. Using data collection tools such as questionnaires, observation of classes and intervention with reading and discussion of the composition The tenement. The researchers began to experience the use made of the literary composition, as well as the difficulties and needs to maintain it. Thus, from the data, they performed the analysis of the prospects surrounding the reading and literary reflection in the classroom. Highlighting the reasons for this practice be always maintained and established as the center of literature classes. After all, the literary reading fosters the referential of life and the knowledge of their readers becoming essential for human development.